FORMATION OF A VALUE PROPOSITION FOR CLIENTS: THEORETICAL APPROACHES AND UNDERSTANDING OF REPRESENTATIVES OF RUSSIAN COMPANIES - A. V. Trachuk; N. V. Linder; V. O. Tuaev (Стратегические решения и риск-менеджмент, 2022)
The paper is devoted to a comparative analysis of theoretical approaches to the formation of a value proposition and its understanding by representatives of Russian companies. The existing theoretical approaches to the formation of a value proposition are considered, as well as the main tools used in its formation in practice. To determine the theoretical approaches, more than 50 articles from leading economic journals were analyzed. To analyze the understanding of the value proposition, Russian companies conducted in–depth semi-structured interviews with managers of 84 Russian and foreign companies representing customer service departments, sales departments, innovation activities, strategic management, marketing and brand management departments.The analysis has shown that for most employees of companies, the concepts of a value approach in management and a value proposition are limited to standard categories, such as price, quality, and direct satisfaction of needs. This is especially true for representatives of Russian companies and firms that conduct their business only within Russia and CIS countries. While representatives of international companies noted the importance of the entire range of value formation tools in one way or another evenly, respondents from Russian companies clearly relied on product components and price in their answers. It should also be noted the leadership of product tools in both cases, and if Russian respondents focused only on the quality of the product in their answers, then representatives of international companies often noted the importance of the assortment and uniqueness of products.The result of the study was to determine the importance and place in the process of forming a value proposition of such tools as joint value creation with the consumer and the involvement of personnel in joint value creation.The author's approach to the formation of value proposition by companies is proposed in the article. The proposed matrix model allows you to quickly determine which factors and tools companies need to focus on first.